1967
DOI: 10.1002/jsfa.2740180811
|View full text |Cite
|
Sign up to set email alerts
|

The search for a veterinary insecticide II.—Carbamates active against sheep blowfly

Abstract: Many aryl N-methylcarbamates and their N-acyl derivatives have been prepared and tested against larvae of the sheep blowfly, Lucilia sericata. Mammalian toxicities and persistences on sheep fleece were also determined. The factors which led to the selection of Butacarb (3,5-di-t-butylphenyl N-methylcarbamate) as a new veterinary insecticide are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1968
1968
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that substitution of the hydrogen atom on the carbamyl nitrogen of insecticidal methylcarbamate esters by different functional groups such as acyl (Fraser et al, 1967), dialkoxyphosphinothioyl (Fahmy et al, 1970), alkyl-and arylsulfenyl (Black et al, 1973), aminoeulfenyl (Fukuto et al, 1975), and symmetrical and asymmetrical NJf•-thiobiscarbamates (Fahmy et al, 1974(Fahmy et al, ,1978 almost always results in compounds of lower mammalian toxicity compared to the parent methyl- showed good insecticidal activity, in some cases being superior to the parent material against certain insects. Derivatization of insecticidal methylcarbamates generally resulted in compounds of lower anticholinesterase activity and different physical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that substitution of the hydrogen atom on the carbamyl nitrogen of insecticidal methylcarbamate esters by different functional groups such as acyl (Fraser et al, 1967), dialkoxyphosphinothioyl (Fahmy et al, 1970), alkyl-and arylsulfenyl (Black et al, 1973), aminoeulfenyl (Fukuto et al, 1975), and symmetrical and asymmetrical NJf•-thiobiscarbamates (Fahmy et al, 1974(Fahmy et al, ,1978 almost always results in compounds of lower mammalian toxicity compared to the parent methyl- showed good insecticidal activity, in some cases being superior to the parent material against certain insects. Derivatization of insecticidal methylcarbamates generally resulted in compounds of lower anticholinesterase activity and different physical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from various laboratories have shown that substitution of the hydrogen atom on the carbamoyl nitrogen of insecticidal methylcarbamate esters by different functional groups such as acyl (Fraser et al, 1967), dialkoxyphosphinothioyl (Fahmy et al, 1970), alkyl-and arylsulfenyl (Black et al, 1973), aminosulfenyl (Fukuto et al, 1975), symmetrical and asymmetrical , '-thiobis-(carbamate)s (Fahmy et al, 1974(Fahmy et al, , 1978, and N-sulfinyl (Fahmy and Fukuto, 1981) almost always produced compounds of lower mammalian toxicity compared to the parent methylcarbamates. Derivatization of insecticidal methylcarbamates also resulted in compounds of lower anticholinesterase activity and with physical properties different from those of the parent methylcarbamates (Black et al, 1973;Fahmy and Fukuto, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…3,5-Di-tert.-butylphenyl N-methylearbamate, m.p. 102°C, was prepared from 3,5-di-tert.-butylphenol and methyl isocyanate in ether (Fraser et al 1967;Metcalf & Fukuto, 1965). A sample of [3H]Butacarb was that prepared by Douch & Smith (1971) and had a specific radioactivity of 0.1Ci/mol.…”
Section: Methodsmentioning
confidence: 99%
“…Butacarb, 3,5 -ditert. -butylphenyl -Nmethylcarbamate, is an insecticide of particularly low mammalian toxicity but is extremely toxic to larvae of the sheep strike blowfly Lucilia sericata (Fraser, Greenwood, Harrison & Wells, 1967). It has, for an insecticide of this type, a long persistence on fleece and seemed a possible altemative to dieldrin or the more poisonous organophosphates in sheep dips.…”
mentioning
confidence: 99%